Validation of Senescence of the Role of ATM/P53 Pathway in Myocardial Senescence in Mice with Sepsis - Yan Z; Shi X; Ding R; Xia F; Du Y; Wang X; Peng Q (Infection and Drug Resistance)
Zhonghan Yan,1,* Xuemei Shi,1,* Ruilin Ding,2 Fenfen Xia,1 Yan Du,3 Xiaojie Wang,4 Qing Peng1 1Department of Cardiology, The Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People’s Republic of China; 2Institute of Drug Clinical Trial/GCP Center, The Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People’s Republic of China; 3Department of Cardiology, Deyang People’s Hospital, Deyang, Sichuan, People’s Republic of China; 4Department of Endocrinology, Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaojie Wang, Department of Endocrinology, Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of China, Email 46601661@qq.com Qing Peng, Department of Cardiology, The Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of China, Email qingpeng9712118@163.comBackground: Sepsis induces multi-organ damage, including myocardial dysfunction, which is often reversible. However, the role of cell senescence in sepsis-induced myocardial dysfunction (SIMD) remains understudied. This study aimed to investigate gene expression changes related to myocardial aging in sepsis.Methods: Transcriptomic datasets (GSE79962 and GSE141864) were analyzed to identify senescence-related genes (SRGs) by intersecting differentially expressed genes (DEGs) with the CellAge database. Functional enrichment and protein-protein interaction (PPI) network analysis were performed to identify key pathways and hub genes. A murine sepsis model was established via intraperitoneal lipopolysaccharide (LPS) injection, and the Ataxia Telangiectasia Mutated Protein (ATM) inhibitor KU60019 was used to assess the effects on cardiac function and cellular aging.Results: Bioinformatics analysis revealed 15 aging-related genes, including MYC, TP53, CXCL1, and SERPINE1, which were upregulated in septic myocardial tissue. Functional enrichment analysis highlighted pathways related to DNA damage repair, cell senescence, and immune response. In vivo validation using murine LPS-induced sepsis models confirmed significant myocardial damage, which was alleviated by treatment with KU60019, an inhibitor of the DNA damage response pathway.Conclusion: Cellular senescence and immune dysregulation play critical roles in SIMD. Targeting DDR pathways, as demonstrated by KU60019 treatment, provides novel insights into the role of cellular senescence in severe sepsis and its potential therapeutic implications for improving cardiovascular prognosis in septic patients.Keywords: sepsis-induced myocardial dysfunction, cell senescence, transcriptome, key genes, database, ATM/P53 pathway